Kennkarte, Vorname, Passe: Wichtige Daten und Tatsachen (C.V. Zeitung, 1938)
Newspaper article from C.V.-Zeitung (Central-Verein-Zeitung), a Jewish newspaper published in Berlin from 1922-1938, with a table of regulations for identification cards, first names, and passports for German-Jewish people. The chart lists the laws, who it affects, the authority, deadlines, and any special provisions.
Keywords: Antisemitism; Jews; Jewish Holocaust (1939-1945); Third Reich; German newspapers; Newspapers; Jewish newspapers